Future Smart Food: Rediscovering Hidden Treasures of Neglected and Underutilized Species for Zero Hunger in Asia - Li, Xuan (2018)
Xuan Li IFPRI-FAO conference side event, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand